Pengaruh Kapasitas Fiskal Daerah terhadap Kinerja Dinas Kependudukan dan Pencatatan Sipil Provinsi Maluku dalam Mencapai Target Nasional - Arief Rahman; Mohamad Arsad Rahawarin; Hendry Selanno (MAN 4 Kota Pekanbaru, 2025)
This study analyzes the influence of regional fiscal capacity on the performance of the Civil Registration and Population Service (Disdukcapil) of Maluku Province in achieving national administrative targets. Using a descriptive qualitative approach, data were obtained through interviews, document reviews, and field observations. The results show that fiscal capacity significantly supports operational activities, service infrastructure, and outreach programs, particularly for remote island communities. Nevertheless, fiscal capacity alone does not determine performance outcomes. Leadership, coordination, and service innovation also play crucial roles. Despite fiscal limitations, Disdukcapil has adopted adaptive strategies to sustain service delivery, though disparities in access persist. Strengthening fiscal policy, optimizing transfer funds, and improving governance capacity are essential for sustainable and equitable population services. This study contributes to the understanding of fiscal dynamics and public service performance in geographically dispersed regions.